2014
DOI: 10.1242/dev.096875
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 is required for lineage priming in the developing inner cell mass of the mouse blastocyst

Abstract: The transcription factor Oct4 is required in vitro for establishment and maintenance of embryonic stem cells and for reprogramming somatic cells to pluripotency. In vivo, it prevents the ectopic differentiation of early embryos into trophoblast. Here, we further explore the role of Oct4 in blastocyst formation and specification of epiblast versus primitive endoderm lineages using conditional genetic deletion. Experiments involving mouse embryos deficient for both maternal and zygotic Oct4 suggest that it is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(138 citation statements)
references
References 41 publications
8
128
2
Order By: Relevance
“…Thus mouse mutants of many of the genes that are coexpressed at early stages, such as Oct4, Nanog and Gata6, can develop past these early time points and can undergo some aspects of lineage specification [49][50][51][52][53]. Hence, individually, these factors may not be explicitly required for sustaining a totipotent state.…”
Section: Gene Regulatory Network and Totipotencymentioning
confidence: 99%
“…Thus mouse mutants of many of the genes that are coexpressed at early stages, such as Oct4, Nanog and Gata6, can develop past these early time points and can undergo some aspects of lineage specification [49][50][51][52][53]. Hence, individually, these factors may not be explicitly required for sustaining a totipotent state.…”
Section: Gene Regulatory Network and Totipotencymentioning
confidence: 99%
“…The silencing of OCT4 causes the formation of blastocysts lacking a pluripotent ICM (Table 1), thus with developmental potential restricted to trophoblastderived lineages (Nichols et al, 1998). Curiously, trophoblast cells require paracrine signaling from pluripotent cells, to retain their bona fide state and viability (Nichols et al, 1998;Le Bin et al, 2014). Although cleavage-stage embryonic development occurs without OCT4, the segregation between epiblast and primitive endoderm is extinguished in ICM cells lacking OCT4 (Le Bin et al, 2014).…”
Section: Octamer-binding Transcription Factor 4 (Oct4)mentioning
confidence: 99%
“…Curiously, trophoblast cells require paracrine signaling from pluripotent cells, to retain their bona fide state and viability (Nichols et al, 1998;Le Bin et al, 2014). Although cleavage-stage embryonic development occurs without OCT4, the segregation between epiblast and primitive endoderm is extinguished in ICM cells lacking OCT4 (Le Bin et al, 2014).…”
Section: Octamer-binding Transcription Factor 4 (Oct4)mentioning
confidence: 99%
“…However, unlike Sox2, Oct4 expression does not become restricted to the Epi after implantation [20,111]. Recent studies have demonstrated that Oct4 is required for the maintenance of PrE-specific gene expression, which is disrupted in the absence of zygotic OCT4 protein [59,60]. Notably, this requirement for Oct4 cannot be rescued by exogenous FGF, demonstrating that Oct4 acts downstream of FGF signalling and plays a cell-autonomous as well as non-cell-autonomous role in PrE specification [59,60].…”
Section: (B) Regulatory Network Governing the First Cell Fate Choicesmentioning
confidence: 99%